Relação entre urbanização e integridade biótica de florestas nativas. - Peixoto-Giacon, Vanessa (2019)
Facing the unbridled anthropic actions, the fragmentation and disturbance of urban forest fragments have been causing, on a global scale, the decline of species populations, genetic losses, extinction processes, reduction of ecosystem services and contributing to climate change. It is necessary to evaluate how much urban forests are impacted by the urbanization process, and under what conditions they can or cannot, to continue over time. Therefore, the objective of this research was to analyze if there is a relation between the environmental quality of urban forest fragments and the presence of urbanized areas in the surroundings. The diagnosis of environmental quality was performed in seven native forest fragments, in Southeastern Brazil, through the application of a Biotic Integrity Index (IIB) on the spot. Considering the complexity of the landscape, the analyses were structured combining the land use and cover survey, landscape indices (AREA, PARA-Ratio, SHAPE, ENN and NEAR) and the biotic integrity index (IIB) of the analyzed fragments. For this, two analysis scales were adopted: (1) landscape scale and (2) fragment scale (or local scale). In the landscape scale, the data showed that there was a relationship with the size of the urban forest fragment and its biotic integrity, as well as the inversely proportional relationship between integrity and perimeter/area, that is, the smaller the perimeter the larger the IIB, showed. There is also shown the lack of relationship between fragment shape and distance from the nearest neighbor with biotic integrity, as well as the proximity of the urbanized area with the IIB. In the fragment scale, the hypothesis of this study was corroborated, demonstrating that there is a relationship between the quality of urban forest fragments and the urbanized area, validating that the distance from the urbanized area influenced the increase of epiphytes, diameter and height of the trees, as well as late species in the canopy, which indicate good biotic integrity. In contrast, the fragments near the urban area and the edge obtained an increase in the presence of clearings, lianas, grasses, dead trees and exotic species, variables that are bad indications for biotic integrity, impairing the preservation of local biodiversity and maintenance of ecosystem services. Finally, it is strategically recommended the management remnants of urban forest, promoting the improvement of their environmental quality, seeking to mitigate the effects of urbanization, and thus preserve their capacity to remain in the landscape.